2006
DOI: 10.1002/cncr.22156
|View full text |Cite
|
Sign up to set email alerts
|

Creating the environment for a successful community partnership

Abstract: This paper describes the development of the American Indian Oncology Program (AIOP) and presents the accomplishments of a participatory research approach that involved an integrated network for cancer care and research. AIOP used a participatory process to develop infrastructure, identify research questions, develop methodologies, write supplemental grants, and evaluate accomplishments based on community defined measures of success. Partnerships between University and Indian Health Service, private, and state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…50 Engaging users to identify, design and deliver interventions is recommended to remedy current unhealthy lifestyles and lack of engagement with health messages. 51,52 We identified barriers to family-based physical activity which align with the levels described in Bronfenbrenner's socio-ecological model. 31,40 We also found that some issues cross the ecological levels: work patterns and income (exosystem) affect individual isolation and well-being (microsystem); and the quality of built environments and neighbourhood facilities (mesosystem) was associated with socio-economic characteristics (macrosystem).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…50 Engaging users to identify, design and deliver interventions is recommended to remedy current unhealthy lifestyles and lack of engagement with health messages. 51,52 We identified barriers to family-based physical activity which align with the levels described in Bronfenbrenner's socio-ecological model. 31,40 We also found that some issues cross the ecological levels: work patterns and income (exosystem) affect individual isolation and well-being (microsystem); and the quality of built environments and neighbourhood facilities (mesosystem) was associated with socio-economic characteristics (macrosystem).…”
Section: Discussionmentioning
confidence: 89%
“…Few physical activity‐based interventions have targeted both mothers and fathers of young children, or have focused on facilitators and barriers to parent and child physical activity in the community . Engaging users to identify, design and deliver interventions is recommended to remedy current unhealthy lifestyles and lack of engagement with health messages …”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have called CBPR a best practice in American Indian communities (Burhansstipanov, Christopher, & Schumacher, 2005; Caldwell et al, 2005; Coe, Wilson, Eisenberg, Attakai, & Lobell, 2006; Kaur, Dignan, Burhansstipanov, Baukol, & Claus, 2006; Noe et al, 2007; Strickland, 2006), largely because of historic abuses by medical and other researchers (Burhansstipanov et al, 2005). Many have asserted that the majority of American Indian communities prefer CBPR to other research methods, and some communities mandate its use.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15] Community-based participatory research (CBPR) could be viewed as one such organizational collaborative approach, as it is based upon the principles of co-learning between community and research institution members, shared power in decision making, and actions targeting fundamental structural changes for the community. [16][17][18][19][20][21][22][23] The mechanism of CBPR is collaboration between community and university researchers, a highly integrated form of connection that is rooted in interorganizational theories. Many current efforts to reduce health disparities, such as the Centers for Disease Control and Prevention's REACH 2010 (Racial and Ethnic Approaches to Community Health by the year 2010) initiative and the National Cancer Institute's Community Network Programs, have their basis in CBPR.…”
mentioning
confidence: 99%
“…Many current efforts to reduce health disparities, such as the Centers for Disease Control and Prevention's REACH 2010 (Racial and Ethnic Approaches to Community Health by the year 2010) initiative and the National Cancer Institute's Community Network Programs, have their basis in CBPR. [16][17][18][19][20][21][22][23][24][25] While collaborative efforts have become common, there are few methods to assess and track the effectiveness of these collaborations. In the interorganizational field, network analysis can assess the degree to which and by whom information and other goods are exchanged in the network.…”
mentioning
confidence: 99%